2017
DOI: 10.4103/0976-9668.210009
|View full text |Cite
|
Sign up to set email alerts
|

A simple way for the preparation of natural antioxidant quercetin from rutin by subcritical water

Abstract: Context:Quercetin (QR) is a natural strong antioxidant of the plant origins. It is used for treating conditions of heart and blood vessels including “hardening of arteries” (atherosclerosis), high cholesterol, heart disease, circulation problems, preventing cancer, for treating chronic infections of the prostate, etc.,Aims:The aim of this work was to development and study of an acid-free technique for the preparation of QR from rutin (RT) that requires no use of acids and toxic organic solvents.Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Recently, the authors have shown that in a subcritical water medium in a temperature range 180-220 °C a hydrolysis of rutin to quercetin took place (Fig. 2) [14][15][16]. According to the literature [17], quercetin is more active against the AChE enzyme than its glycoside rutin.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, the authors have shown that in a subcritical water medium in a temperature range 180-220 °C a hydrolysis of rutin to quercetin took place (Fig. 2) [14][15][16]. According to the literature [17], quercetin is more active against the AChE enzyme than its glycoside rutin.…”
Section: Resultsmentioning
confidence: 98%
“…At the same time, it should be noted that an increase of the temperature of subcritical water from 120 to 220 °C causes a change in the physicochemical characteristics of water [7,14]. Therefore, one can expect an increase in the solubility of plant metabolites, on the one hand, and the chemical transformation of polyphenols from the native OL, on the other hand.…”
Section: Resultsmentioning
confidence: 99%